Hydrolysis of the phosphoanhydride linkage of cyclic ADP-ribose by the Mn2+-dependent ADP-ribose/CDP-alcohol pyrophosphatase - Canales, J (2009)
Cyclic ADP-ribose (cADPR) metabolism in mammals is catalyzed by NAD glycohydrolases (NADases) that, besides forming ADP-ribose, form and hydrolyze the N1-glycosidic linkage of cADPR. Thus far, no cADPR phosphohydrolase was known. We tested rat ADP-ribose/CDP-alcohol pyrophosphatase (ADPRibase-Mn) and found that cADPR is an ADPRibase-Mn ligand and substrate. ADPRibase-Mn activity on cADPR was 65-fold less efficient than on ADP-ribose, the best substrate. This is similar to the ADP-ribose/cADPR formation ratio by NADases. The product of cADPR phosphohydrolysis by ADPRibase-Mn was N1-(5-phosphoribosyl)-AMP, suggesting a novel route for cADPR turnover.